Professional Fulfillment: Ideas and Expectations of Pre-Graduate Student Nurses - Aneliya Chifligarska; Makreta Draganova (Journal of Biomedical & Clinical Research)
The objective of this study was to investigate the attitudes and expectations of fourth-year student nurses regarding their professional fulfillment after completing basic education. A questionnaire survey was carried out in six higher educational institutions in the Republic of Bulgaria - Pleven, Sofia, Varna, Stara Zagora, Plovdiv, and Ruse. Almost half of the students involved (114, 49.10%), planned to apply for a master’s degree in management of health care, and 62 (26.70%) preferred fulfillment abroad. Concerning the place of work, 80 (34.50%) of the respondents wished to specialize in surgical care. Of this latter group, 108 (46.60%) expressed the opinion that they would obtain excellent training in surgical units, and 62 (26.70%) expected to like the specificity of work in such units. The most significant influence on professional orientation in the area of surgical care of the future nurses was that of the tutors from the clinical bases - 90 (38.80%).